Pendapatan Usahatani Kelapa Di Desa Jiko Belanga Kecamatan Nuangan Kabupaten Bolaang Mongondow Timur - Mangoli, Agreishe Septaharani; Katiandagho, Theodora Maulina; Porajow, Oktavianus (AGRI-SOSIOEKONOMI, 2023)
This study aims to calculate the income of coconut farming in Jiko Belanga Village, Nuangan District, East Bolaang Mongondow Regency. This research was conducted during September 2022. The data used in this research are primary data and secondary data. Primary data was obtained through direct interviews with 10 respondents using a questionnaire. And secondary data obtained through books, journals, and literature related to this research topic. The results of this study indicate that the average income received by the farmers of Jiko Belanga Village, Nuangan District, East Bolaang Mongondow Regency with coconut farming for one harvest/per quarter (3 months) with copra production of IDR4,956,517. and income per hectare is IDR2,065,215.